2011
DOI: 10.1177/0091270010372627
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation With Argatroban for Elective Percutaneous Coronary Intervention: Population Pharmacokinetics and Pharmacokinetic-Pharmacodynamic Relationship of Coagulation Parameters

Abstract: The synthetic direct thrombin inhibitor argatroban has a rapid onset and offset of anticoagulation. However, there are no data about the pharmacokinetic-pharmacodynamic (PK-PD) relationship of argatroban in patients undergoing contemporary percutaneous coronary intervention (PCI) and no data about other coagulation parameters than activated clotting time (ACT) in this setting. In the ARG-E04-trial, 140 patients were randomly assigned to argatroban (250, 300, or 350 µg/kg as bolus before PCI, followed by 15, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
9
0
4
Order By: Relevance
“…There seems to be a consistent dose-effect relationship using argatroban, regardless of the assay used. A study evaluating the pharmacokinetic-pharmacodynamic relationship of argatroban 92 showed that in contrast to UFH, argatroban causes a faster response in all coagulation parameters (a quicker increase after initiation and normalization after stopping medication). This study also concluded that ACT is the most appropriate method for monitoring the effect of argatroban in patients undergoing PCI.…”
Section: Argatrobanmentioning
confidence: 99%
“…There seems to be a consistent dose-effect relationship using argatroban, regardless of the assay used. A study evaluating the pharmacokinetic-pharmacodynamic relationship of argatroban 92 showed that in contrast to UFH, argatroban causes a faster response in all coagulation parameters (a quicker increase after initiation and normalization after stopping medication). This study also concluded that ACT is the most appropriate method for monitoring the effect of argatroban in patients undergoing PCI.…”
Section: Argatrobanmentioning
confidence: 99%
“…Dans les TIH, l'utilisation grandissante de l'argatroban a permis de mieux définir la posologie à l'initiation du traitement 0,5 à 1 g/kg par minute, puis son ajustement dans les deux heures suivantes à l'aide de la mesure du TCA et/ou du dosage de l'argatroban (Hemoclot-Hyphen Biomed) [45]. Le TCA ne doit pas dépasser 100 secondes.…”
Section: Argatrobanunclassified
“…Le retentissement de l'argatroban sur les tests de coagulation et ses caractéristiques pharmacocinétiques ont été très attentivement analysés dans une étude récente chez des patients ayant une PCI [45].…”
Section: Argatrobanunclassified
See 1 more Smart Citation
“…Herein, we describe a method for direct quantitation of argatroban in plasma samples using a rapid ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) assay with a greater analytical measurement range than previously reported LC-MS/MS methods [6,7,11]. The UPLC-MS/MS method is compared to a commercially available, Hemoclot Thrombin Inhibitors [HTI] (HYPHEN BioMed) indirect activity-based clotting assay for argatroban measurement and recommendations are made with regards to clinical utility and advantages of each method.…”
Section: Introductionmentioning
confidence: 99%